The Employment Effects of Countercyclical Infrastructure Investments - Lukas Buchheim; Martin Watzinger (Center for Economic Studies and ifo Institute (CESifo), 2017)
We estimate the causal impact of a sizable German infrastructure investment program on employment at the county level. The program focused on improving the energy efficiency of school buildings, making it possible to use the number of schools as an instrument for investments. We find that the program was effective, creating one job for one year for each exteuro25'000 of investments. The employment gains reached their peak after nine months and dropped to zero quickly after the program's completion. The reductions in unemployment amounted to two-thirds of the job creation, and employment grew predominately in the construction and non-tradable industries.
Keywords: E24; E62; H72; J23; 330; infrastructure investments; job creation; employment dynamics; countercyclical fiscal policy